Getting to Yes-Means-Yes: Re-thinking Responses to Rape and Rape Culture on College Campuses - Eleanor Christie Gourley (Washington University Journal of Law & Policy, 2016)
This Note looks at how a complementary system of transitional justice and Truth and Reconciliation Commissions (TRCs) may help shift the cultural mentality of rape and sexual assault and provide recourse and closure for individuals who suffered assaults prior to the effective date of California’s Affirmative Consent Law (ACL). Gourley addresses the climate and context of sexual assault on college campuses and California’s Affirmative Consent law and compares it to the strengths and weaknesses of TRCs using two examples: South Africa and Sierra Leone. Gourley argues for the use of TRCs in conjunction with the ACL to encourage a shift in the discourse surrounding sexual assault on college campuses.
Keywords: rape culture; sexual assault; South Africa; Sierra Leone; Truth and Reconciliation Commissions; college campuses; transitional justice; California; Affirmative Consent Law